Attachment styles and depression among nursing officers of tertiary care centre in India - Mamta; Parihar, Aashish; Kumar, Ashok (International Journal of Research in Medical Sciences, 2025)
Background: The concept of attachment plays a relevant role in mental health. Attachment style refers to how a person perceives and experiences interpersonal relationships. There are various attachment styles or patterns through which an individual attaches or form relationships with others. Attachment has a persistent and long-term impact on depression. The main aim of the study is to assess the attachment styles and depression among nursing officers of tertiary care centre in India. Methods: Descriptive research design was used. The study was conducted at all India institute of medical sciences (AIIMS), Jodhpur among 250 nursing officers selected by convenient sampling technique. Self-structured attachment style questionnaire was used to assess the attachment style and structured questionnaire centre for epidemiologic studies depression scale was used to assess the depression among nursing officers. Data analysis was done by using statistical package for social sciences-version 25 (SPSS-25). Frequency, percentage, mean, standard deviation, chi square test, Fisher exact test and Pearson correlation were used. Results: Result revealed that out of 250, majority 213 (85.2%) nursing officers had secure attachment style. Majority 183 (73.2%) nursing officers were normal, showed no depression. Moderate negative correlation was there between secure attachment style and depression scores. Strong positive correlation was found between anxious attachment style and depression scores. There was moderate positive correlation between avoidant, fearful attachments and depression scores respectively. Conclusions: The study indicates that majority of nursing officers were having secure attachment style and were normal, showed no depression. The study established a relationship between attachment style and depression.